2020
DOI: 10.32587/jnic.2020.00255
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Early Hyperglycemia in Neurocritically Ill Patients

Abstract: Objective To evaluate the relationship of early hyperglycemia and neurological prognosis in neurocritically ill patients. Methods This was a retrospective study of adult patients admitted to the neurosurgical intensive care unit (ICU) from January 2010 to July 2019. Primary outcome was neurological status at 6-month follow-up assessed with the Glasgow Outcome Scale (GOS, 1 to 5). Results A total of 202 patients were analyzed in this study. Of them, 70 (34.7%) patients had early hyperglycemia (≥200 mg/dL within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This leads to impaired aerobic glycolysis and intracellular acidosis that in turn cause a secondary toxic-ischemic effect on the brain (7). The association between these metabolic alterations and outcomes of pediatric TBI have been investigated in several single-center studies (2,5,8,9). These prior single-center studies have identified admission hyperglycemia as an important predictor of mortality in pediatric TBI (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to impaired aerobic glycolysis and intracellular acidosis that in turn cause a secondary toxic-ischemic effect on the brain (7). The association between these metabolic alterations and outcomes of pediatric TBI have been investigated in several single-center studies (2,5,8,9). These prior single-center studies have identified admission hyperglycemia as an important predictor of mortality in pediatric TBI (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%